HUBUNGAN TINGKAT KECANDUAN DENGAN TINGKAT KECEMASAN PELAKU JUDI ONLINE DI WILAYAH KECAMATAN TOROH - Lilis Wahkidi; Emilia Puspitasari S; Mariyati mariyati; Tamrin Tamrin (Jurnal Ilmu Keperawatan Komunitas, 2022)
Background: In the current era of globalization, phenomena that occur in social life are faced with certain patterns of social behavior in which people tend to experience changes along with the development of an era that is completely complex due to technological advances. The development of information technology is increasingly modern, apart from making it easier to carry out internet activities, it can also be used in a different way, namely online gambling. Gambling itself is a bet that is done intentionally, namely by risking one value or something that is considered valuable by realizing that there is a risk. This needs to be addressed from various angles because the impact will be felt when the user has entered the addiction phase which is continuously carried out unconsciously and is self-defeating. Addiction is an excessive behavior in which users will continue to do this and find it difficult to stop, this can cause a person to be isolated from their environment, tend to get bored quickly and experience anxiety. Anxiety is a mental health disorder characterized by feelings of worry, anxiety or fear that are strong enough to interfere with daily activities. The purpose of this study is to analyze the relationship between the level of addiction and the level of anxiety of online gambling players in the Toroh District area. Research Methods: The type of research used is a quantitative method with a non-experimental approach, with a cross-sectional design where data collection for the independent and dependent variables is carried out at the same time. The research instrument used was a questionnaire in the form of a google form. The study population consisted of 78 respondents who were taken using simple random sampling technique. The analysis test used is Rank Spearman. Results: The results obtained were a p value = 0.000, which means that Ha was accepted and the results of Rho = -0.423, which means that the correlation is in the weak category (correlation value 0.2-0.4) in a negative direction, meaning that the higher the level of addiction to online gambling, the more bad level of anxiety online gamblers.